Kadar Polifenol Total pada Teh Hijau (Camellia Sinensis) Menggunakan Ekstraksi Maserasi dengan Perbandingan Pelarut Etanol – Air - Dwi Evitasari; Erna Susanti (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2021)
Green tea is a kind of plant that have an active polyphenol substance. Polyphenol is a group of compounds that has a role as a natural antioxidant. Solvent comparison used affects the extracted polyphenol content. This study aims to compare the total polyphenol content in green tea from maceration method with solvent concentration variation of 30%, 50%, and 70%. In this research, green tea is extracted by using the maceration method with ethanol – water solvent concentration of 30%, 50%, and 70%. The total polyphenol content determination in green tea was conducted by using the Follin-Ciocalteu method by UV-Vis spectrophotometre, and using gallic acid as a standard. According to this research, the yield calculation of ethanol extract in green tea with the ethanol concentration of 30%, 50%, and 70% are 41.220%; 39.979 %; and 47.971 %. The total polyphenol content test of green tea with the ethanol concentration of 30%, 50%, and 70% are 11.294 mg GAE/100 g; 16.377 mg GAE/100g; and 15.640 mg GAE/100 g. The anova statistical analysis result shows that there is a significant difference of total polyphenol content of green tea extract with ethanol concentration 30% and 50%, also there is no significant difference in the ethanol concentration of 70%. The highest result of total polyphenol of green tea extract with the ethanol concentration of 50%. It is suggested to conduct a further study on the type of the polyphenol substance in green tea.